Determination of Operational Threshold for Coding and Modulation Combination to Improve The Quality of High Throughput Satellite in Ka-Band Frequency in Indonesia - M. Pasaribu; Heroe Wijanto; Budi Prasetya (JMECS (Journal of Measurements, Electronics, Communications, and Systems), 2016)
The vast enhancement of telecommunication technology has encouraged the increase of demand for more satellite capacity. HTS in Ka-Band frequency, that can deliver more capacity up to 50 GHz, can be a solution. Unfortunately, Ka-Band is susceptible to rain attenuation which is potentially difficult to be implemented in Indonesia because of its high rain rate. But, According to the previous research by Suwadi, Marrudani, and Lye, the combination of coding and modulation technique can be used as a solution to improve the performance of service dealing with rain attenuation. In this research, the writer will try to improve whether the combination of coding and modulation is also able to improve HTS Ka-Band communication link here ini in Indonesia with the high rain rate per year and to determine threshold of which the combination of coding and modulation that is best suited to each weather condition, in order to get the minimum required performance with BER min = 10 − 8. The conclusion of this research shows that the quality of HTS in Ka-Band frequency in Indonesia with BER = 10 − 8 can be improved by using QPSK, 8-APSK, 16-APSK, and 9 types of FEC. Furthermore, the 17 pairs of ModCod can be categorized into 8 thresholds that will determine with that ModCod that should be used in order to get the link quality of BER = 10 − 8 for each certain rain condition.